Cultivating Interest in Reading the Qur'an of MTs Al-Ghozali Jatibarang Students Through the Qiro'ati Method - Darojatul Maula; Didik Himmawan (Aslama: Journal of Islamic Studies, 2024)
The qira'ati method is a method of learning the Qur'an directly which is read with tartil and pays attention to the rules of tajwid science. This qira'ati method is also applied at MTs Al-Ghozali Jatibarang, hoping that by implementing this method, students will find it easier to understand the material because after each material is given, students immediately practice directly or imitate what the teacher directs so that it can foster interest in reading the Qur'an of students at MTs Al-Ghozali Jatibarang. In this study, the method used is a qualitative research method, namely a descriptive research method. The method of collecting data for this study is by means of observation and interviews. The results of this study indicate that; first, the qira'ati method applied at MTs Al-Ghozali Jatibarang is by directly practicing the material that has just been given by reading or imitating the teacher and also by individual submission. Second, the way to foster students' interest in reading at MTs Al-Ghozali Jatibarang is by providing motivation and advice to students about the benefits of reading the Qur'an for themselves and their parents in the world and in the hereafter. And finally, the advantages of the qira'ati method at MTs Al-Ghozali Jatibarang are that learning focuses on students by means of direct practice and individual contributions, while the disadvantages are that there is a feeling of lack of enthusiasm in students.